Controlled continuous systemic heparinization increases success rate of artery-only anastomosis replantation in single distal digit amputation: A retrospective cohort study. Issue 26 (June 2016) - Lee, Jun Yong; Kim, Hak Soo; Heo, Sang Taek; Kwon, Ho; Jung, Sung-No
Abstract : Abstract: Replantation is a prime indication for distal digital amputation, as it helps restore hand aesthetics and functions; however, venous anastomosis is often not feasible. Previous studies used systemic anticoagulation in distal digital artery only anastomosis replantation surgery to improve replantation success rate, however, which yielded limited level of clinical evidence. This study aimed to compare controlled continuous heparinization (CCH) and intermittent bolus heparinization (IBH) for surgical outcome and clinical variables after single distal digital artery only anastomosis replantation surgery. A single-institution, retrospective cohort study was performed. Out of 324 patients who underwent digital replantation surgery, we focused the study for the Zone I and II single distal digital amputation patients excluding confounding factors. Sixty-one patients were included in this study and underwent artery-only anastomosis replantation surgery with postoperative CCH (34 patients) or IBH (27 patients) protocols. The CCH group targeted activated partial thromboplastin time (aPTT) at 51 to 70 seconds, monitoring aPTT levels every eight hours and administering 100 mg of aspirin per day. The IBH group received 300 mg of aspirin per day and underwent IBH (12, 500 U). Both groups received intravenous prostaglandin E1 drips (10 μg). To verify the factors affecting the success rate of the heparin protocol, patient factors, clinical factors, and operative factors were extracted from the medical records. Statistical analysis with inverse probability of treatment weights propensity score methods compared treatment outcomes and clinical variables. The CCH group's replantation success rate was higher (91.17% vs 59.25%), and the transfusion rate was increased ( P = 0.032). However, the significant decrease in hemoglobin levels (>15%) did not differ between the groups ( P = 0.108). Multivariable logistic regression analysis with potent univariate variables ( P  < .10) revealed that CCH was a statistically significant variable in replantation success rate ( P = 0.004). Neither the major bleeding complications nor the significant decrease in patients' platelet levels were observed in both groups. Our study suggests that CCH after artery-only anastomosis replantation surgery in Zone I and II distal digital replantation is a safe method to improve the replantation success rate and may provide a guideline for use of the anticoagulation method following artery-only anastomosis distal digital replantation surgery. Abstract : Supplemental Digital Content is available in the text